Fibrin-Rich and Platelet-Rich Thrombus Formation on Neointima: Recombinant Tissue Factor Pathway Inhibitor Prevents Fibrin Formation and Neointimal Development following Repeated Balloon Injury of Rabbit Aorta - Asada, Yujiro; Hara, Seiichiro; Tsuneyoshi, Atsushi; Hatakeyama, Kinta; Kisanuki, Atsushi; Marutsuka, Kousuke; Sato, Yuichiro; Kamikubo, Yu-ichi; Sumiyoshi, Akinobu (Thrombosis and Haemostasis, 1998)
Thrombus formation and neointimal growth are the critical events in restenosis after balloon angioplasty. However, the responses of diseased vessels to injuries caused by balloon angioplasty have not been well examined. We investigated the thrombus formation and neointimal development following the balloon injury to the previously induced neointima in the rabbit aorta and the effects of recombinant tissue factor pathway inhibitor (rTFPI) on these responses. Rabbit thoracic aortas were subjected to injury with a Fogarty 4F balloon catheter at 1.75 atm (first injury), and 4 weeks later the same vessels were subjected to the second injury with a Swan-Ganz 5F balloon catheter at 1.4 atm (mild-injury group) or 1.8 atm (severe-injury group), and immediately after that a retrograde bolus injection of rTFPI (100 μg/kg body weight) or saline was performed into the injured segments via the central tube of the Swan-Ganz catheter. Twenty minutes after the second injury, the injured surfaces were covered with platelet-rich thrombi in the mild-injury group and with fibrin-rich thrombi in the severe-injury group. Damaged intimal smooth muscle cells, which were immunohistochemically positive for tissue factor (TF), were observed beneath the fibrin-rich thrombi. The neointima 4 weeks after the second injury was significantly thicker in the severe-injury group than in the mild-injury group. The bolus infusion of rTFPI markedly inhibited fibrin formation on the injured surfaces, and significantly reduced the neointimal development in the severe-injury group at 4 weeks after the second injury. These results indicate that TF-dependent coagulation pathway is primarily responsible for fibrin-rich thrombus formation and may play an important role in neointimal development following the balloon injury to the rabbit aortic neointima. Additionally the bolus administration of rTFPI to the injured vessels could prevent mural thrombus formation and neointimal growth after balloon angioplasty.